Comparative proteomics analysis of Pichia pastoris cultivating in glucose and methanol - Rui Hou; Linhui Gao; Jianhui Liu; Zhen Liang; Yongjin J. Zhou; Lihua Zhang; Yukui Zhang (Synthetic and Systems Biotechnology, 2022)
The methylotrophic yeast Pichia pastoris (syn. Komagataella phaffii) has been extensively engineered for protein production, and is attracting attention as a chassis cell for methanol biotransformation toward production of small molecules. However, the relatively unclear methanol metabolism hampers the metabolic rewiring to improve the biosynthetic efficiency. We here performed a label-free quantitative proteomic analysis of Pichia pastoris when cultivated in minimal media containing methanol and glucose, respectively. There were 243, 158 up-regulated proteins and 244, 304 down-regulated proteins in log and stationary phase, respectively, when cultivated in methanol medium compared with that of glucose medium. Peroxisome enrichment further improved the characterization of more differentially expressed proteins (481 proteins in log phase and 524 proteins in stationary phase). We demonstrated the transaldolase isoenzyme (Tal2, Protein ID: C4R244) was highly up-regulated in methanol medium cultivation, which plays an important role in methanol utilization. Our work provides important information for understanding methanol metabolism in methyltrophic yeast and will help to engineer methanol biotransformation in P. pastoris.